(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
This article focuses on the basic concepts and phonation patterns of nonverbal speech, including the opinions of scholars who have conducted research on phonetic forms of nonverbal speech, and definitions of phonetic forms of nonverbal speech. The phonetic type of nonverbal speech includes timbre, tempo, speed, pitch, intonation, pause, the melody of speech, dialectical, social articulatory features of sound.